Strategi Peningkatan Kinerja Karyawan Di Pdam Giri Tirta Dalam Penyediaan Air Bersih Di Kota Gresik - Nisa’, Rosyidah Aulan; Hidayati, Roziana Ainul (Jurnal Mahasiswa Manajemen, 2025)
Background – Employees are overwhelmed to solve problems in the field because employees in the distribution division and customer disruptions are also short of manpower so it will be difficult to optimize their performance. Objective – This study aims to determine the factors that hinder the performance of employees at the Regional Drinking Water Company in Gresik Regency in providing clean water and to analyze strategies for improving the performance of employees of the Gresik Regency Drinking Water District in providing clean water, which currently may not be in accordance with the expectations of all communities. Design/ Methodology/ Approach – This study used a qualitative research approach using data validity testing by means of memberchecks, and data collection techniques using interviews. The data analysis technique used in this research is descriptive qualitative analysis. Findings – The results showed that there was 1) factors inhibiting employee performance in terms of quality, quantity, and time, as well as the existence 2) strategies to improve employee performance in terms of quality, quantity, and time. Research Implication – Factors that hinder employee performance in serving the community quickly and responsively and keeping their promises accurately, and lack of empathy for the needs of the community. Limitations – The researcher urges to conduct further and deeper research related to the phenomenon of employee performance improvement strategies using different techniques.